2019
DOI: 10.32615/ps.2019.048
|View full text |Cite
|
Sign up to set email alerts
|

The role of inoculum identity for growth, photosynthesis, and chlorophyll fluorescence of zinnia plants by arbuscular mycorrhizal fungi under varying water regimes

Abstract: This experiment aimed to determine effects of three arbuscular mycorrhizal fungi (AMF), i.e., Rhizophagus irregularis, Rhizophagus intraradices, and Funneliformis mosseae, either singly or their mix inoculation on dry mass, photosynthesis, chlorophyll (Chl) fluorescence, leaf pigment contents, and water-use efficiency (WUE) in Zinnia elegans (var. Magellan Red) plants under different water regimes (WR). The greenhouse experiment was performed under a complete randomized design at four different WR [100% of fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…This result may imply that mycorrhizal seedlings suffered less disorder in the electron transport chain than nonmycorrhizal seedlings [38]. In addition, AMF inoculation also increased qN significantly under moderate salt stress, and we thought AMF inoculation might increase the utilization of absorbed light and minimize the dissipation of light energy [39]. Thus, due to their higher PSII efficiency than that of nonmycorrhizal seedlings, mycorrhizal seedlings were more tolerant of moderate salt stress (100 and 150 mM NaCl).…”
Section: Plos Onementioning
confidence: 76%
“…This result may imply that mycorrhizal seedlings suffered less disorder in the electron transport chain than nonmycorrhizal seedlings [38]. In addition, AMF inoculation also increased qN significantly under moderate salt stress, and we thought AMF inoculation might increase the utilization of absorbed light and minimize the dissipation of light energy [39]. Thus, due to their higher PSII efficiency than that of nonmycorrhizal seedlings, mycorrhizal seedlings were more tolerant of moderate salt stress (100 and 150 mM NaCl).…”
Section: Plos Onementioning
confidence: 76%
“…Consequently, sustainable practices for managing crop production have been emphasized worldwide in recent years. AMF is one of the most widely used symbiotic associations for the promotion of plant growth and the resistance of plants to salt [42,44,45]. To explore the potential function of AMF in flax plants under abiotic stress, the present research examined growth, physiological, biochemical, and yield parameters, as well as nutrient distribution within the plants exposed to salt stress and AMF inoculation.…”
Section: Discussionmentioning
confidence: 99%
“…Total content of phenols was increased by Glomus versiforme in maize under two drought regimes, indicating that AMF-induced phenols, as active scavengers of ROS, protect cellular structures and the functioning of their hosts (Begum et al 2019). Numerous studies have confirmed that AMF inoculation enhances concentrations of carotenoids in Aloe barbadensis, Citrus aurantifolia, Ricinus communis and Zinnia elegans under drought stress (Zhang et al 2018b;Bagheri et al 2019;Khajeeyan et al 2019;Nejad et al 2019). An increase in carotenoids in droughtstressed host plants by AMF inoculation could quench more 1 O 2 from excess light energy, thereby protecting the photosynthetic machinery from photo-oxidative damage (Shi et al 2015).…”
Section: Plant Response Mechanisms On Amf-mitigating Ros Burst Under Drought Stressmentioning
confidence: 99%